Less Meat Initiatives: An Initial Exploration of a Diet-focused Social Innovation in Transitions to a More Sustainable Regime of Meat Provisioning - Morris, Carol; Kirwan, James; Lally, Rhonwen (The International Journal of Sociology of Agriculture and Food, 2014)
Meat production and consumption as currently configured in developed countries is seen by a growing number of actors as compromising food system sustainability, with the situation likely to worsen as globally meat consumption is predicted to double by 2050. This article undertakes an initial investigation of less meat initiatives (LMIs), which have recently emerged to encourage a reduction in meat eating at a number of different sites and scales. Prominent examples include Meat Free Mondays and Meatless Mondays, which have originated in the UK and the US respectively. Drawing on the socio-technical transitions literature, the article conceptualizes the notion of eating less meat as a predominantly civic-based social innovation, focused on diet, with LMIs representing socially innovative niche projects that have the potential to facilitate a transition towards a more sustainable regime of meat provisioning. Initial empirical evidence derived from primary and secondary sources is used to examine the ‘diffusion’ of LMIs, both in the UK and internationally. A key conclusion is that although LMIs are both replicating and scaling-up they are not translating the idea of eating less meat in any significant way into the mainstream, principally because their demands are too radical. A further conclusion is that while commercial organizations, the media and the state continue to promote high and unsustainable levels of meat consumption, the ability of LMIs to facilitate the diffusion of an innovative social practice – eating less meat – is likely to be limited. Nevertheless, LMIs do have the potential for raising awareness of and fostering debate about meat eating and the arguments for reducing overall levels of meat consumption.